Analysis of The Influence of Brand Ambassador in Building Brand Image on The Purchase Decision of Samsung Smartphone Products Customers - Abdul Manap; Yusmita Hawari; Andriani Lubis; Zurlina Lubis; Asep Saepullah (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The rapid development of technology makes communication even easier. Communication can be done through many devices, one of which is a smartphone. Nearly 70% of people in Indonesia already use smartphones from various brands. This study attempts to examine how brand ambassadors contribute to brand image development and how they affect consumer choices. The route analysis method was utilized to process the data from the 100 respondents who participated in this study. The findings of this study demonstrate that brand ambassadors have a direct impact on brand perception. Purchase decisions are directly influenced by brand ambassadors and brand perception. Through their representation of the company, brand ambassadors indirectly influence consumer purchasing decisions.